MOBILE WEB IMPLEMENTATION AS MEDIA INFORMATION SYSTEM IN MARGODADI VILLAGE - Ristanto, Firgiawan; Astuti, Tiara Widya; Handoko, Dwi; Syarifuddin, Ahmad; Nanda, Adi Prasetia; Phang, Fatin Aliah (Universitas Islam Negeri Raden Intan Lampung, 2022)
At this time the mobile web information system has been widely used for various kinds of activities, one of which is for information on the village. Information systems using the mobile web can make it easier for the village to provide information to the community. In providing information related to the village, Margodadi Village still uses a manual system or by asking the community directly to the village office to obtain information. Therefore, Margodadi Village must change the manual system to a mobile web information system so that it is more efficient and effective in providing information to the community about village-related information. In this problem, the researcher tries to model an information system for media information provided to the community related to mobile web-based village information. Researchers in modelling the new system use the SLDC method. With the existence of a new information system in providing information to the mobile web-based community, it is hoped that it can help make it easier for the Margodadi Village to provide information to the community so that the community can easily get information related to Margodadi Village information.